2020
DOI: 10.1088/1755-1315/429/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The utilization status of Yellowfin Tuna (Thunnus albacares) in Morotai Island Regency

Abstract: Morotai Island Regency is located in the adjacent of three National Fisheries Management Area of Indonesian Republic (WPPNRI 715, WPPNRI 716, WPPNRI 717). Geographically Morotai Island’s waters lie in two Indonesian hydro-oceanography phenomenon, namely Throughflow and Eddy Halmahera which affect the abundance of marine resources. This study aims to determine the utilization status of Yellowfin Tuna (Thunnus albacares) in Morotai Island regency including: catch per unit effort (CPUE), maximum sustainable yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…This is crucial as one of the solutions to ensure sustainable utilization of flying fish eggs. The suggestion to utilize fishery resources according to the TAC has been echoed by various researchers focusing on specific fish species, ranging from global waters [33,34] to Indonesia [35,36,37,38,39]. Our study is limited to revealing the production of flying fish eggs, so further research is needed to assess the fishery resources, uncovering the potential value and the level of comprehensive utilization of flying fish resources.…”
Section: Efforts In Capture Flying Fish Egg Production and Annual Cpu...mentioning
confidence: 99%
“…This is crucial as one of the solutions to ensure sustainable utilization of flying fish eggs. The suggestion to utilize fishery resources according to the TAC has been echoed by various researchers focusing on specific fish species, ranging from global waters [33,34] to Indonesia [35,36,37,38,39]. Our study is limited to revealing the production of flying fish eggs, so further research is needed to assess the fishery resources, uncovering the potential value and the level of comprehensive utilization of flying fish resources.…”
Section: Efforts In Capture Flying Fish Egg Production and Annual Cpu...mentioning
confidence: 99%
“…The information confirms that tuna fisheries are a potential and profitable resource that drives people in many countries to exploit the fish extensively. Some studies have revealed a decrease in tuna fiaheries in some areas [28,29,30]. Based on the potency of tuna fishery as a driving force and the tuna fishermen as a pressure , then conceptual model based on DPSIR was consructed to propose a management strategy for sustainable small-scale tuna fishery (Figure 4).…”
Section: Management Strategy For Sustainability Of Small-scale Tuna F...mentioning
confidence: 99%
“…Penangkapan tuna oleh nelayan di Kabupaten Pulau Morotai pada umumnya merupakan usahausaha berskala kecil, yang dilakukan menggunakan pancing ulur dan tonda dengan durasi trip satu hari (one day fishing) (Siahainenia, Apituley, & Bawole, 2021;Sofiati & Alwi, 2019;Talahatu et al, 2020. Usaha-usaha ini menghadapi masalah bisnis yang terkait dengan sejumlah faktor, di antaranya ketergantungan pada musim penangkapan, keterbatasan armada penangkapan, dan belum adanya kebijakan yang memberikan kepastian bagi keberlangsungan usaha (Hikmah & Nasution, 2017).…”
Section: Pendahuluanunclassified
“…Penilaian kualitas daging tuna didasarkan pada tingkat kesegaran. Jika kualitas tidak terpenuhi maka grade ikan akan diturunkan ke grade lokal dan harga jualnya pun akan lebih murah (Talahatu et al, 2020, Wijaya, Huda, & Manadiyanto, 2012…”
Section: Figure 2 Comparison Of Yellowfin Tuna Volume Production In M...unclassified